"Review on the Development of Special Education Since China's Reform and Opening Up" - Zeng, Xueyuan (Journal of Theory and Practice of Social Science, 2024)
Reform and opening up is a major node in China. As an organic part of education, special education is of great significance to all aspects of China's development. In this paper, the software CiteSpace is used as the main analysis tool, and the visual analysis of CNKI database of China Hownet is used as the auxiliary analysis tool, so as to analyze and evaluate 133 Chinese‐related documents about reform, opening up and special education on CNKI database of China Hownet in terms of research hotspots and trends, publishing institutions and authors. Through research, it is found that the development of special education in China is in a downturn since the reform and opening up, and new research hotspots can be found through the analysis of the previous peak development and the analysis of key documents.